PROSES PERANCANGAN ALAT SIMULATOR PNEUMATIC DOUBLE ACTING CYLINDER DENGAN DUA BATANG PISTON MASUK DAN KELUAR - Andi, Andi Ariansyah (Program Vokasi-Universitas Negeri Gorontalo, 2025)
A pneumatic system uses compressed air to produce pressure and provide motion. This system was invented in 1889 by Macron Matic. The pneumatic system simulator tool employs a double-acting cylinder. This research employs engineering design methods to design, manufacture, and test a simulator featuring a double-acting cylinder and two piston rods, enabling manual simulation of piston movement. Results show that among four pressure levels tested, higher air pressure decreases the time required for the piston to retract. However, as pressure increases, the time-saving efficiency lessens. Therefore, choosing an optimal pressure is essential to achieve performance without risking damage to system components. The decrease in time between 3 and 4 bars is smaller than between 1 and 2 bars, indicating that higher pressure yields diminishing returns in piston movement speed. Friction, airflow resistance, and discharge valve efficiency affect the piston's reverse stroke at elevated pressures.